Penerapan Audit Sistem Informasi Proses Penerimaan Peserta Didik Baru (PPDB) Dengan Menggunakan Kerangka Kerja COBIT 4.1 - Nike Alpio Rizky; Setia Ningsih; Intan sari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
. PPDB is the first activity or process in an activity for school institutions, where PPDB goes through a selection determined by the school for prospective new students or student.. Admission of new students is an activity that is carried out routinely in every school, especially when entering the change of semester in the educational calendar each year. This is a very important initial stage in the process of registering prospective students at an educational institution.The aim of this research is to investigate and evaluate in depth how the process of accepting new students takes place at the Darma Bangsa School in Bandar Lampung, using COBIT 4.1 maturity level analysis. COBIT is a collection of the best documents for IT Governance to make it easier for auditors, management and users to become a middle ground between business risks, controls and technical issues.